'A competent mess': food, consumption and retirement at religious houses in England and Wales, c.1502–38. Issue 1 (1st January 2023) - Fizzard, Allison D.
ABSTRACT : This article contributes to our knowledge of food habits in late medieval and early sixteenth-century England and Wales through an analysis of under-examined records of retirement agreements known as corrodies; these were struck between religious houses and individuals or married couples. Corrody texts, copied in records from the Court of Augmentations, are a rich source for patterns of consumption, particularly of beverages and foodstuffs, in the first four decades of the sixteenth century. People from a range of social backgrounds acted as careful consumers in their attempts to guarantee their preferred foods in their retirement years. These late retirement arrangements indicate an evolution of food entitlements in corrodies towards greater specificity in terms of what the corrodians were to receive. They also reflect larger food trends of this period, such as a move away from pottage and a desire to secure access to meat and other animal-derived foods.